2020
DOI: 10.1101/2020.10.14.20206607
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and Validation of a Deep Learning Model for Automated View Classification of Pediatric Focused Assessment with Sonography for Trauma (FAST)

Abstract: The pediatric Focused Assessment with Sonography for Trauma (FAST) is a sequence of ultrasound views rapidly performed by the clinician to diagnose hemorrhage. One limitation of FAST is inconsistent acquisition of required views. We sought to develop a deep learning model and classify FAST views using a heterogeneous dataset of pediatric FAST. This study of diagnostic test developed and tested a deep learning model for view classification of archived real-world pediatric FAST studies collected from two pediat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…They found that ML could distinguish between the presence and absence of hemoperitoneum with a sensitivity of 100% and specificity of 90% and concluded that such DL algorithms can help clinicians interpret trauma USG results. A study applying a customized DL algorithm to USG still images and video clips of pediatric trauma patients showed that, compared to experts, the DL algorithm was able to detect hemoperitoneum in Morrison’s pouch USG images with a sensitivity of 91.9% (95% CI, 91.7–92.1%) and a specificity of 97.9% (95% CI, 97.8–98.0%) [ 32 ]. The authors showed that the accurate classification of USG images via DL algorithms is critical for ensuring the quality and feasibility of multi-level DL FAST models and improving the assessment of injured children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that ML could distinguish between the presence and absence of hemoperitoneum with a sensitivity of 100% and specificity of 90% and concluded that such DL algorithms can help clinicians interpret trauma USG results. A study applying a customized DL algorithm to USG still images and video clips of pediatric trauma patients showed that, compared to experts, the DL algorithm was able to detect hemoperitoneum in Morrison’s pouch USG images with a sensitivity of 91.9% (95% CI, 91.7–92.1%) and a specificity of 97.9% (95% CI, 97.8–98.0%) [ 32 ]. The authors showed that the accurate classification of USG images via DL algorithms is critical for ensuring the quality and feasibility of multi-level DL FAST models and improving the assessment of injured children.…”
Section: Discussionmentioning
confidence: 99%
“…As the concept of “point-of-care USG” is gaining popularity, free fluid in clinical situations is being identified via a comprehensive evaluation of continuous dynamic images rather than by the evaluation of still images. Additionally, the performance of customized DL algorithms in classifying USG images may be better with video clips than with still frames [ 32 ]. Therefore, further research on the performance of AutoML in analyzing USG images from video clips is needed.…”
Section: Discussionmentioning
confidence: 99%
“…
Deep learning (DL) has been applied with success in proofs of concept across biomedical imaging, including across modalities and medical specialties [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . Labeled data is critical to training and testing DL models, and such models traditionally require large amounts of training data, straining the limited (human) resources available for expert labeling/annotation.
…”
mentioning
confidence: 99%